Evaluación del aprovechamiento de la energía producida por la biomasa en cocinas rústicas de uso familiar en hogares de la parroquia San Andrés de la provincia Chimborazo en el año 2013. Determinación de los parámetros de diseño de una cocina mejorada para el uso racional de la biomasa. - Jinez Llangarí, Ramiro Javier (2014)
In the present job a theoretical study is directly performed in the camp, about the use of firewood as fuel in the back wood kitchens in the parish saint Andrew, canton guano, province Chimborazo, with the objective to evaluate the consumption of the biomass energy, to determine the parameters designs of an improved kitchen take advantage from the combustion of firewood like an eucalyptus energy biomass. the statistics permitted to perform an analysis of consumption of firewood in relation of time cooking of the food and the intradomiciliary pollution, in the backwood kitchens, with the data of this study it takes to prototype of a kitchen that meets the characteristics of: minimizing the biomass energy, optimizing the physical space with dimensions and detailed parts that take advantage of natural resources, without invading customs and traditions of consumers, with the support of the technical team from the ONG ADRA (the agency Adventist of development and resources care of Ecuador. this design is built to prove the advantage of the biomass energy in less time reducing the contamination of the homes by improving the lifestyle of people from the parish motive of the study and more with the conversion of the environment